A Critical Analysis of Leadership Approaches, Decision Making, and Innovation by Women in India - Nanda, Simpy (Digital Repository of Theses, 2025)
The proliferation of methodologies run by data has revolutionized the landscape of scholarly inquiry, offering unprecedented opportunities for uncovering insights and advancing knowledge across diverse domains. Within this context, this dissertation explores the intricacies of Women in management and leadership roles: a critical analysis of leadership approaches, decision-making, and innovation by Women, employing a rigorous blend of quantitative analysis, computational techniques, and theoretical frameworks to elucidate key phenomena and address pressing research questions. Central to this endeavor is data analysis, which serves as the cornerstone of empirical research, enabling the extraction of meaningful patterns, trends, and relationships from complex datasets. Moreover, this dissertation transcends traditional disciplinary boundaries, engaging with interdisciplinary perspectives and leveraging insights from fields such as women in the management sector and leadership skills, unveiling the multifaceted nature of women in leadership. Aim of the research is to explore two critical dimensions of women in leadership, shedding light on their diverse leadership styles and the challenges of gender bias and stereotypes they encounter along their journey to the top. A woman in leadership often brings unique qualities and approaches to the table, distinct from their male counterparts—for instance, the case of Maya, a seasoned executive leading a technology firm. Maya's leadership style is characterized by empathy, collaboration, and a focus on nurturing talent within her team. She prioritizes building relationships and fostering a supportive work environment, which cultivates loyalty and enhances team cohesion. Contrast to Maya's approach a male counterpart is in a similar position. While Mark may excel in strategic decision-making and assertiveness, Maya's style emphasizes emotional intelligence and inclusivity. Research suggests that such diverse leadership styles contribute to a more inclusive organizational culture and result in better decision-making and improved performance outcomes. The realm of women in leadership is rich and multifaceted, encompassing a diverse array of leadership styles and confronting a myriad of obstacles along the way. By acknowledging and appreciating the distinct achievements of women in leadership roles and tackling ingrained biases and hurdles, organizations can create a more inclusive and fair setting that enables women to excel and lead with assurance. By persistently advocating, educating, and offering support, we can pave the path towards a future where gender equality in leadership is not merely a goal but a tangible outcome. By adopting a holistic approach to data analysis and interpretation, this study seeks to enrich our understanding of women's role in management and contribute to the broader discourse surrounding it.